The impact of networking on firm performance: Evidence from small and medium-sized firms in emerging technology areas - Matias Kalm (The Research Institute of the Finnish Economy (ETLA), 2012)
Recent developments in the field of network research have led to a growing interest in interorganisational relationships among social science scholars. One of the most important research areas is related to entrepreneurship research and how relationship networks affect firm performance. However, the existing literature focuses mostly on qualitative case studies and quantitative studies that analyse mergers and acquisitions or patent types of data. By analysing connection and causality between activity in co-operational relationships and firm growth, this study seeks to empirically address the following research question: 'How does activity in network relationships influence the growth and internationalisation of technology-based firms in emerging technology areas?' Furthermore, the connection and causality between activity in co-operational relationships and the internationalisation rates of firms are also analysed. This analysis is based on a data set and interviews with 53 small and medium-sized firms. Both a descriptive analysis and regression methods are used to analyse the connection between activity in co-operational relationships and firm growth or internationalisation. Firm growth is measured with both revenue and the employment growth rate. In addition, the activity in in the co-operational relationships is divided into two components: increasing versus consistently high activity with network actors. To address possible causality issues, this research employs activity measures that are based on the importance of the relationships rather than simply the number of relationships. The results show that increasing activity with network actors is positively connected with firm growth as measured in both revenue and employment growth. Furthermore, the results partially support the hypothesis that consistently high activity is positively connected to firm growth. Finally, the results suggest that growth firms positively benefit from increased relationship activity with both current and prospective actors in diverse relationship networks. Moreover, the single most negative result is the relatively low impact of relationship activities on public-sector actors and networks.
Keywords: L14; L25; L26; O43; 330; interorganisational relationships; firm growth; internationalisation; networks